Analysis of performance measurement using the balanced scorecard - Puput Rahmi (Indonesia Auditing Research Journal, 2022)
The research is formulated on describing the performance measurement through balanced scorecard method at Sucofindo cooperative. branch-Palembang. This research is aimed at describing the performance measurement through balance scorecard method at Sucofindo Cooperative, branch Palembang. The research setting was within 5 five years, from 2011 until 2015. The type of this research was a descriptive research in line with determination of the performance of the Sucofndo Cooperative branch Palembang through balanced scorecard method. The data used were primary data and secondary data. This research was a qualitative analysis. The technique of analyzing the data was through balanced scorecard method The results showed that there were some variations in the achievement of result, as the financial perspective to generate earnings / profit and customer's perspective to improve members as well as learning and growth perspective in employee's productivity experience had decreased and not maximum, while for internal business perspective was good enough.